More istoriĭ - Bishop, Sylvia (Chitarium, 2022)
Whenever Roo visits Grandpa, she loves exploring the seaside cove near his cottage. But on her latest stay, Grandpa explains that he can't go down there any more - the path is too steep and overgrown for him to manage. Instead Grandpa tells Roo the stories behind the many objects that fill his house. All of Grandpa's stories feature the cove and Roo realizes that now, even though they're so close to the sea, Grandpa is cut off from it. Is there anything she can do to bring Grandpa to the place he loves the most?